Effect of inhibitors on ethanol production by Pichia stipitis in a complex culture media - Abud, Ana Karla de Souza; Oliveira Junior, Antonio Martins de; Silva, Augusto de Souza da (Acta Scientiarum. Technology, 2017)
Biomass from lignocellulosic material constitutes a promising energy alternative and without competing with food production. However, pretreatments are required for conversion into sugars which release hexoses, pentoses and other sugars, coupled to inhibitors. Current analysis focuses on ethanol production with the three major inhibitors of lignocellulosic biomass pretreatment, namely, acetic acid, furfural and 5-hydroxymetilfurfural (HMF), and investigates the influence of a mixture of these inhibitors on fermentation by Pichia stipits, using commercial xylose as the only carbon source, through a full factorial 23 + 3 design of experiments (DOE). Fermentations were conducted in a laboratory scale, at 150 rpm and 72h, in a complex culture media with xylose and different inhibitor concentrations, based on the experimental analysis of sugarcane bagasse and 2.107 cell mL-1 of initial concentration of the microorganism. Experimental results showed a significant influence of acetic acid concentration, which must be at the lowest possible level, with no influence of furfural and hydroxymethyl furfural respectively up to concentrations 2.25 and 0.75 g L-1. Â